(untitled) (Universal International Scientific Journal, 2026)
The development of a professional pedagogical image is a crucial component in the preparation of future teachers within higher education institutions. This study aims to explore effective approaches to improving the professional pedagogical image of pre-service teachers by identifying key pedagogical, psychological, and environmental factors that influence its formation. The research employs a mixed-methods approach, combining quantitative surveys and qualitative interviews conducted among students of педагогical universities.The findings reveal that the formation of a professional pedagogical image is significantly influenced by factors such as self-reflection, communicative competence, professional motivation, and the acmeological educational environment. In addition, the integration of innovative teaching methods and reflective practices contributes to the enhancement of students’ professional identity and image.The study also highlights the importance of systematic and targeted pedagogical interventions in fostering a positive and sustainable professional image among future teachers. Based on the results, practical recommendations are proposed for higher education institutions to improve teacher training programs. These include the implementation of competence-based approaches, the development of reflective skills, and the creation of supportive learning environments.